[18F]PSMA Tracer and 131I Avid Retroperitoneal Thyroid Tissue in a Patient with Synchronous Thyroid and Prostate Carcinomas: First Case Report and Literature Review - Punchihewa, Chamani; Zeilmaker, Juliette; Elsewafy, Maged; Dizdarevic, Sabina (World Journal of Nuclear Medicine, 2025)
We present the first described case of retroperitoneal metastasis from follicular thyroid carcinoma (FTC). This was incidentally discovered as a PSMA (prostate-specific membrane antigen)-positive lesion on PSMA-positron emission tomography (PET)-computed tomography (CT) in a patient with synchronous prostate cancer (PCa).The expanding utilization of PSMA-PET-CT has revealed tracer uptake in several nonprostatic conditions. A 68-year-old man investigated for PCa, underwent magnetic resonance imaging, which revealed an 18-mm retroperitoneal soft tissue nodule lateral to the left psoas and a left pelvic node. PSMA-PET-CT showed tracer uptake in the primary PCa, retroperitoneal lesion, and pelvic node with an incidental high-grade focus in the thyroid. A CT following a period of androgen deprivation demonstrated no response in the retroperitoneal lesion, while the pelvic node became smaller. Fine-needle aspiration (FNA) of the thyroid was performed, although an ultrasound was initially reported as benign. FNA cytology (FNAC) was interpreted as a benign nodule. However, CT-guided biopsy of the retroperitoneal lesion revealed follicular thyroid tissue. The differential diagnoses were ectopic thyroid tissue and FTC. FNAC and ultrasound were reviewed at the thyroid multidisciplinary meeting (MDM) and upgraded to follicular atypia and suspicious for malignancy, respectively. Left hemithyroidectomy confirmed an angioinvasive follicular carcinoma. Completion thyroidectomy revealed a small incidental micropapillary carcinoma. Single photon emission computed tomography (SPECT)-CT post-131I treatment showed intensely iodine-avid tissue within the thyroid bed and retroperitoneal deposit. On follow-up 123I-SPECT-CTs, there was no abnormal iodine uptake and the retroperitoneal deposit decreased from 18 to 5 mm, presumed as scar tissue. Thyroglobulin reduced from 7.7 to < 0.1 ug/L. MDM recommended 6 monthly surveillance. PSMA-positive lesion evaluation can be challenging due to PSMA expression in nonprostatic conditions. As illustrated by this case, unusual distribution of tracer uptake requires further investigations and a multidisciplinary approach to guide management. High PSMA expression in differentiated thyroid cancer was associated with shorter progression-free survival and may be considered a marker of aggressiveness. Such tumors could be candidates for targeted PSMA-radioligand therapy (e.g., 177lutetium), particularly in radioiodine-negative/refractory cases, which are difficult to treat.
Keywords: PSMA-PET-CT; synchronous malignancies; thyroid cancer; prostate cancer; retroperitoneal metastasis; diagnostic pitfalls